Analisis Faktor-faktor yang Mempengaruhi Keputusan Pembelian Produk Perumahan Pada PT. Mandevilla Payakumbuh - Vivi Gustri Wahyuni; Baginda Parsaulian; Sandra Dewi; Cahya Agung Maulana (Pustaka Digital Indonesia, 2026)
The background of this research is based on consumers feeling hesitant in buying a house, namely the lack of transparent information about product development and quality, this causes uncertainty that has the potential to reduce consumer confidence, as well as the existence of consumers who want an environmentally friendly lifestyle. This study aims to analyze how product quality, belief, and Green lifestyle affect the decision to purchase a house in PT. Mandevilla is growing. This research is a field study with a qualitative approach. Data is not collected in the form of numbers. The data source consists of primary and secondary data, which is collected through observation, interview, and documentation techniques. The research informants consisted of six consumers of PT. Mandevilla, who was asked about product quality, beliefs, and green lifestyles, focusing on key points relevant to the research. The results of the study show that product quality, trust, and Green lifestyle are the elements that influence consumers' decisions in buying a house in PT. Mandevilla is growing. High quality attracts consumers to make a purchase. With the attention, honesty, and understanding of the developer, consumer trust can increase. This encourages buying interest. Houses with green and environmentally friendly concepts can improve the comfort and health of residences, so that they can encourage consumers to buy. The conclusion of this study is that product quality, trust, and Green lifestyle are factors influencing home purchase decisions. Developers need to improve product quality, honesty, and attention so that consumers feel satisfied with their purchases.